FakeDetect: Bangla fake news detection model based on different machine learning classifiers - Sraboni, Tasnuba; Uddin, Md. Rifat; Shahriar, Fahim; Rizon, Ruhit Ahmed; Polock, Shakib Ibna Shameem (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.